Hubungan Mutu Pelayanan Terhadap Kepuasan Pasien di Poli Fisioterapi RSU Siti Hajar - Sulaiman, Sulaiman; Anggriani, Anggriani (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2019)
Good hospital services so far still seem difficult to obtain by the community when they want to seek treatment for services. Good service is a very important thing to improve patient satisfaction especially in poly physiotherapy at Siti Hajar Hospital Medan. This type of research was descriptive with a